Voltage Flicker Mitigation using a simplified STATCOM model suitable for long time simulations - Agüero, Jorge Luis (2011)
Voltage fluctuations caused by fast changes of industrial loads have been a major concern for both power companies and customers in the area of power quality. The fast response of the Static Compensator (STATCOM) makes it an efficient solution for improving power quality in distribution systems. This paper describes a simplified model for PWM-based STATCOM used in a distribution system for mitigation of voltage fluctuations produced by an Electric Arc Furnace (EAF). The analyzed system is modeled using MATLAB/SIMULINK Power System Blockset (PSB), including a complete STATCOM model with its power circuits and its control system. Static and dynamic performance of STATCOM is evalueates and voltage fluctiation mitigation studies are performed and discussed. The voltage fluctuation mitigation is obtained by simulations and according to international stardards.